Modern methods of treating neurological diseases - Krzysztof Bednarz; Bartosz Basiaga; Sara Trojan; Marek Leśniak; Jakub Kwieciński; Sławomir Miszuda; Agnieszka Błaszczyk; Urszula Fussek-Styga; Agata Szwedkowicz; Jakub Heluszka (Quality in Sport, 2023)
Aim of the article